V siju mesečine Ustno izročilo Lokve, Prelož in bližnje okolice - Čok, Boris (Studia Mythologica Slavica Supplementa, 2012)
The book ['In the moonlight glow. Outlines of mythic characters in the villages of Lokev and Prelože in the context of Slavic mythology'] is a rarity on the European scale in the field of pre-Christian beliefs. What makes it so valuable is that it is a first-hand record of these beliefs, as they were told to the author by people close to him, grandmothers, grandfathers and villagers, who preserved their old-faith beliefs and rituals until the last century. The book is therefore an inexhaustible source of old- faith practices, beliefs, sacred places and other folklore traditions in the villages Lokev, Prelože and their immediate neighborhood. As such, it is one of the main sources of study in Slavic mythology, as well as in general and monument to the integration of karst-nature and its people.